Navigating climate change complexity and deep uncertainty: approach for building socio-ecological resilience using qualitative dynamic simulation - Merino-Benítez, Tatiana; Bojórquez-Tapia, Luis Antonio; Miquelajauregui, Yosune; Batllori-Sampedro, Eduardo (Frontiers in Climate, 2024)
The consequences of climate change on different sectors of society are interrelated. The threats posed by rising global temperatures, intensifying extreme weather events, and shifting climatic patterns are becoming increasingly evident all around the world. Policymakers face the daunting task of assessing climate change risks, encompassing impacts and response strategies, to guide sustainability transformations. In this study, we introduce a four-step qualitative Decision Making Under Deep Uncertainty (DMDU) approach in the context of Climate Change Impact Assessments (CCIA). Our goal is to enhance the integration of CCIA into spatial planning, particularly in the Global South, which is characterized by poor infrastructure. Emphasizing the value of qualitative DMDU, we explore vulnerability and resilience through a lens of multi-sectoral and multi-scalar socio-ecological processes. We exemplify our approach by applying CCIA to the coastal zone of Yucatán, Mexico, accounting for social and environmental heterogeneity across the four Regions in which it is administered. Our methodology stands as a valuable tool for optimizing the allocation of climate change mitigation and adaptation policies.